Testing the role of the Himalaya Mountains as a dispersal barrier in freshwater gastropods (Gyraulus spp.). (3rd April 2013) - von, Parm Viktor; Albrecht, Christian; Riedel, Frank; Bössneck, Ulrich; Zhang, Hucai; Wilke, Thomas
<x xml:space="preserve">Abstract</x> The Himalayas are considered to constitute a biogeographical boundary between the Palaearctic and Oriental regions. However, this mountain range does not form a uniform barrier because several large river valleys deeply cut into the Himalayas, crossing drainage divides and potentially forming dispersal corridors, particularly for freshwater organisms. In the present study, the effectiveness of these corridors is tested for the first time based on molecular data, using the amphi‐Himalayan freshwater gastropod genus Gyraulus as a model group. Based on a broad spatial sampling from the Himalayas and the Tibetan Plateau, phylogenetic analyses were performed using mitochondrial DNA sequence data. The resulting phylogeny shows that northern and southern Himalayan clades are geographically distinct (i.e. they exclusively consist of either northern or southern specimens). This pattern suggests a lack of gene flow across the Himalayas probably at least since the late Pliocene/early Pleistocene. Successful dispersal and/or establishment of gastropods might have been impeded by geographical and ecological features. Instead of direct dispersal across the range, multiple colonizations of regions north and south of the Himalayas from extralimital areas have to be assumed. The Himalayas thus represent a very strong dispersal barrier for freshwater snails, and probably for other taxa as well. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 109, 526–534.